2003
DOI: 10.1076/ceyr.26.2.107.14516
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of dispase causes retinal hemorrhages in rabbit and human eyes

Abstract: Retinal hemorrhages were evident as early as 11 min after injection. It is suggested that this enzyme degraded selectively basement membrane components without affecting other proteins involved in the vitreous-retinal junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
1
16
1
1
Order By: Relevance
“…20 In rabbit eyes in vivo and in human eyes 15 min before enucleation, intravitreal injection of dispase caused intraretinal haemorrhages and ILM disruption at bleeding sites. 22 In this series, there was no effect of dispase on PVD induction.…”
Section: Hyaluronidasementioning
confidence: 60%
See 1 more Smart Citation
“…20 In rabbit eyes in vivo and in human eyes 15 min before enucleation, intravitreal injection of dispase caused intraretinal haemorrhages and ILM disruption at bleeding sites. 22 In this series, there was no effect of dispase on PVD induction.…”
Section: Hyaluronidasementioning
confidence: 60%
“…20 The enzyme has been shown to effectively induce PVR in rabbits in a dosedependent fashion, known as the dispase model of PVR, and future studies need to investigate the safety of dispase before clinical studies can be considered. 22,23 Plasmin Plasmin is a non-specific serine protease mediating the fibrinolytic process. It acts also on a variety of glycoproteins including laminin and fibronectin, both of which are present at the vitreoretinal interface.…”
Section: Hyaluronidasementioning
confidence: 99%
“…Not only would this facilitate surgery, but it may prevent disease if performed early in the natural history. Various pharmacologic vitreolysis agents have been tested to date, [21][22][23][24][25][26][27][28][29] but little is known about the exact mechanism of action of these substances, and so far none has met with sufficient success to result in widespread use. Plasmin has been used only in limited series of uncontrolled clinical testing (two published series of nine and seven cases), chondroitinase was used only on 20 patients in a Phase I FDA trial, and hyaluronidase has recently failed a Phase III FDA trial.…”
Section: Pharmacologic Vitreolysismentioning
confidence: 99%
“…Dispase is an interesting case in point. Although two pig studies 24,28 initially showed efficacy and safety, the results of a more extensive recent study 29 in rabbit and human eyes found that dispase caused retinal toxicity, perhaps due to the broad range of proteins subject to its enzyme action. Thus, rather than employing a single broad-acting substance such as microplasmin or dispase, a combination of highly specific agents, such as collagenase, hyaluronidase, or chondroitinase, may be safer and more effective.…”
Section: Figure 17mentioning
confidence: 99%
“…No entanto, estudos realizados pelo nosso grupo em animais e humanos, constataram a ocorrência de hemorragias retinianas nas doses relatadas no trabalho original de Tezel et al A presença de hemorragias sugere que a dispase também é capaz de digerir a membrana basal dos capilares da retina, não sendo específica para os componentes da junção vítreo-retiniana (17) .…”
Section: -Dispaseunclassified